Sharing diversity: exchanging seeds and experiences of community seedbanks in South Africa - Matelele, Lehlogonolo Abner; Sema, R.P.; Maluleke, Nkat Lettie; Tjikana, Thabo T.; Mokoena, Mpolokeng Lydia; Dibiloane, M.A.; Vernooy, Ronnie (Bioversity International/Department of Agriculture, Forestry and Fisheries (RSA), 2018)
This report describes the main activities carried out in 2017. The community seed banks of Gumbu and Sterkspruit increased the number of accessions, reproduced seeds of a number of priority crop varieties and strengthened their technical and organizational capacities. They also participated in the first community seed bank exchange and learning workshop that brought together farmers and officials from various provinces. A new community seed bank was set up in Northwest province. Farmers and staff of the Department of Agriculture, Forestry and Fisheries and Bioversity International shared their experiences in a number of (inter) national events. The accumulated experiences of establishing and supporting community seed banks in South Africa were used as input for the development of two community seed bank manuals, one for facilitators and one for farmers. The three community seed banks established so far will support the Department of Agriculture, Forestry and Fisheries’ strategy on conservation and sustainable use of Genetic Resources for Food and Agriculture both in situ and ex situ.